2003
DOI: 10.4141/p02-030
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in irrigated fenugreek grown for forage in rotation with other annual crops

Abstract: ) is an annual legume that has potential as a forage crop on the Canadian Prairies. Experiments were established to determine the tolerance of fenugreek to several herbicides and their efficacy on various weeds. Potentially, fenugreek could be grown in conservation tillage systems in rotation with other annual crops. Therefore, additional multi-factor experiments were conducted to determine the effect of herbicides, seeding method, and 11 previous crops on fenugreek yield. Without herbicide application, weeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
(12 reference statements)
2
24
0
Order By: Relevance
“…The results suggest that either imazethapyr or ethalfluralin at the standard rate could be used for weed control in alfalfa, arrowleaf, balansa, berseem and crimson clover, black lentil, fenugreek, pea, hairy and winter vetch, barrel, snail, and strand medic. These results are in agreement with findings of a recent study in Lethbridge (Moyer et al 2003) that yields of alfalfa and fenugreek treated with imazamox/imazethapyr or trifluralin are usually similar to those from hand-weeded plots. In the study of Moyer et al (2003), the digestibility and protein content of forage was significantly lower in the weedy check than in the imazamox/imazethapyr treatment indicating that weed control in annual legumes is essential.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…The results suggest that either imazethapyr or ethalfluralin at the standard rate could be used for weed control in alfalfa, arrowleaf, balansa, berseem and crimson clover, black lentil, fenugreek, pea, hairy and winter vetch, barrel, snail, and strand medic. These results are in agreement with findings of a recent study in Lethbridge (Moyer et al 2003) that yields of alfalfa and fenugreek treated with imazamox/imazethapyr or trifluralin are usually similar to those from hand-weeded plots. In the study of Moyer et al (2003), the digestibility and protein content of forage was significantly lower in the weedy check than in the imazamox/imazethapyr treatment indicating that weed control in annual legumes is essential.…”
supporting
confidence: 83%
“…These results are in agreement with findings of a recent study in Lethbridge (Moyer et al 2003) that yields of alfalfa and fenugreek treated with imazamox/imazethapyr or trifluralin are usually similar to those from hand-weeded plots. In the study of Moyer et al (2003), the digestibility and protein content of forage was significantly lower in the weedy check than in the imazamox/imazethapyr treatment indicating that weed control in annual legumes is essential. The imazamox/imazethapyr treatments controlled green foxtail, wild oat and redroot pigweed in most years (Moyer et al 2003).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Those studies have revealed the enormous potential of fenugreek as an alternative forage crop for areas with a temperate climate such as that of the Western Canadian prairie. Besides its use for forage production, the annual nature of fenugreek may provide producers an opportunity to use fenugreek as a break crop in crop rotations (Moyer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%